RETRACTED: Di Paola et al. Environmental Risk Assessment of Dexamethasone Sodium Phosphate and Tocilizumab Mixture in Zebrafish Early Life Stage (Danio rerio). Toxics 2022, 10, 279 - Davide Di Paola; Jessica Maria Abbate; Carmelo Iaria; Marika Cordaro; Rosalia Crupi; Rosalba Siracusa; Ramona D’Amico; Roberta Fusco; Daniela Impellizzeri; Salvatore Cuzzocrea; Nunziacarla Spanò; Enrico Gugliandolo; et al. (Toxics)
The journal retracts the article “Environmental risk assessment of mixture of COVID-19 treating pharmaceutical drugs in zebrafish early life stage (Danio rerio)” [...]